Virtue Ethics: St Maximos the Confessor and Aquinas Compared - Louth, Andrew (Studies in Christian ethics, 2013)
Traditionally Christian ethical reflection has taken the form of what is called nowadays ‘virtue ethics’. This article compares the approach to virtue ethics in the Byzantine thinker, Maximos the Confessor, and the Western thinker, Thomas Aquinas. They both share the heritage of Plato and Aristotle. Maximos develops a concern for the virtues that is practical and ascetic; although he recognizes and uses the traditional classical terminology, he prefers a new Christian terminology, based more directly on the Scriptures. In contrast, Aquinas accepts and uses the classical terminology, adding to it Christian ‘theological’ virtues. His concern is much less directly practical than Maximos, and more directed to the kind of society in which the virtues can flourish. This contrast between the ascetical and political (which should not be overdrawn) is manifest in Dumitru Stăniloae and Josef Pieper, introduced as modern interpreters of Maximos and Thomas respectively.